DEMOKRASI LOKAL DI SUMATERA BARAT Memahami Pendekatan “Self Governing Community” Pada Sistem Pemerintahan Nagari Modern di Minangkabau - Amaliatulwalidain Amaliatulwalidain (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Nagari Government in Minangkabau is one of the traditional government based on a self-governing community. In the past, when there has been no modern state, villages are already implementing a democratic system that is based on values and religious customs (adat basandi syarak, syarak basandi Qur'aan) primarily regulate people's lives. In government Traditional Nagari, Nagari led by a prince elected deliberation in traditional institutions with the involvement of elements of the existing indigenous representative Dinagari (Ninik Mamak, Ulema, Cadiak Clever, Bundo Kanduang and Youth). When MasaOrde New with the enactment of Law No. 5 of 1979 on Village Governance, government Nagari underwent a change governance system, from the traditional government toward modern government, Nagari then changed its name into the village, causing the traditional government (self governing community) based on customs Nagari be hilang.Pasca Reform, with the advent of Law No. 22 of 1999 on Regional Autonomy, provide an opportunity to revive the Nagari government implemented through the Regional Regulation No. 10 Year 2000 on the Principles of Nagari administration, which officially marks the West Sumatra back again to the system Nagari administration (self governing community). Keywords : Local Democracy, Self Governing Community, Government Nagari Modern